Slurry for non-aqueous secondary battery and method for producing the same, battery member for non-aqueous secondary battery and method for producing the same, and non-aqueous secondary battery
Through the degassing process of reducing the carbon dioxide concentration, the problem of unstable coating of slurry for non-aqueous secondary batteries in the inkjet method is solved, the manufacturing efficiency and bonding strength of the secondary batteries are improved, and the stable bonding material is achieved distributed.
Patent Information
- Application Number
- CN201980039534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-24
- Filing Date
- 2019-07-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-07-23
AI Technical Summary
When manufacturing a non-aqueous secondary battery using the inkjet method, the coating property is prone to be unstable due to the nozzle blockage, which reduces the manufacturing efficiency of the secondary battery.
By reducing the dissolved carbon dioxide concentration of the mixture containing the particulate polymer and water, the degassing process is performed to suppress nozzle blockage, and the slurry for non-aqueous secondary battery is stably coated in the inkjet method to ensure uniformity of the bonding material distributed.
The surface of the battery member is stable under the inkjet method, which improves the manufacturing efficiency and bonding strength of the secondary battery, and avoids the problem of nozzle clogging.
Smart Images

Figure BDA0002829940210000291
Abstract
Description
Technical Field
[0001] The present invention relates to a slurry for a non-aqueous secondary battery and a method for producing the same, a battery member for a non-aqueous secondary battery and a method for producing the same, and a non-aqueous secondary battery. Background Art
[0002] Non-aqueous secondary batteries such as lithium-ion secondary batteries (hereinafter sometimes referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. In addition, secondary batteries generally have battery components such as a positive electrode, a negative electrode, and a separator that separates the positive electrode from the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.
[0003] When manufacturing such a secondary battery, the battery components of the secondary battery, such as electrodes and spacers, have always been bonded to each other to form a secondary battery laminate. Here, the bonding of the battery components to each other is carried out by, for example, manufacturing a battery component with an adhesive material on the surface and bonding the battery component to other battery components. Moreover, the battery component with an adhesive material on the surface can be made in the following manner: a secondary battery slurry formed by dispersing and / or dissolving an adhesive polymer (adhesive material) in a solvent is applied to the surface of the battery component and then dried.
[0004] For example, in Patent Document 1, organic particles having a core-shell structure having a core and a shell are used as a bonding material. Here, the polymer constituting the core and the polymer constituting the shell have a predetermined electrolyte swelling degree, respectively. Moreover, in Patent Document 1, a battery component having an adhesive layer is manufactured by applying and drying a slurry containing the above-mentioned organic particles, and the battery component having the adhesive layer is bonded to other battery components to manufacture a secondary battery laminate. In addition, the obtained secondary battery laminate is sealed in a battery container together with an electrolyte, thereby manufacturing a secondary battery.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: International Publication No. 2015 / 198530. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Here, in order to firmly bond the battery components to each other and improve the manufacturing efficiency of the secondary battery, the inventor focuses on the inkjet method in which the secondary battery slurry used to form the adhesive material is ejected from the nozzle as tiny droplets and supplied to the surface of the battery component. In addition, the inventor attempts to apply the secondary battery slurry containing granular polymers such as organic particles described in Patent Document 1 to the surface of the battery component by the inkjet method, and the secondary battery slurry on the surface of the battery component is dried to manufacture a battery component with an adhesive material. However, according to the research of the inventor, when the secondary battery slurry containing granular polymers such as organic particles described in Patent Document 1 is applied to the surface of the battery component by the inkjet method, the coating property sometimes becomes unstable due to nozzle clogging, and the manufacturing efficiency of the battery component and even the secondary battery is reduced.
[0010] That is, the above-mentioned prior art still has room for improvement in terms of ensuring strong adhesion between battery members and stably applying the secondary battery slurry to the surface of the battery member even when using an inkjet method or the like.
[0011] Therefore, an object of the present invention is to provide a slurry for a non-aqueous secondary battery which is less likely to clog the nozzle even when an inkjet method is used and which can be stably applied to the surface of a battery member, and a method for producing the same.
[0012] Another object of the present invention is to provide a battery member for a non-aqueous secondary battery using the slurry for a non-aqueous secondary battery of the present invention, and a method for producing the same.
[0013] Furthermore, an object of the present invention is to provide a non-aqueous secondary battery having the battery member for a non-aqueous secondary battery of the present invention.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive research to solve the above problems. Then, the present inventors found that the slurry obtained by reducing the dissolved carbon dioxide concentration of the mixture containing the particulate polymer (A) and water can suppress the clogging of the nozzle and stably apply it to the surface of the battery component even when the above-mentioned inkjet method is used, thereby completing the present invention.
[0016] That is, the present invention aims to solve the above-mentioned problems advantageously, and the method for producing a slurry for a non-aqueous secondary battery of the present invention is characterized in that it includes a degassing step for reducing the concentration of dissolved carbon dioxide in a mixture containing a particulate polymer (A) and water. According to the production method of the present invention, even when an inkjet method is used, a non-aqueous secondary battery slurry can be provided that can suppress nozzle clogging and can be stably applied to the surface of a battery component compared to the case where the mixture is directly used without degassing.
[0017] In addition, the method for manufacturing the slurry for non-aqueous secondary batteries of the present invention preferably performs degassing in the degassing step until the dissolved carbon dioxide concentration of the mixture is 0.01 mg / ml or more and 0.08 mg / ml or less. If degassing is performed until the dissolved carbon dioxide concentration of the mixture is within the above range, a non-aqueous secondary battery slurry with further improved coating properties can be obtained.
[0018] In addition, the present invention aims to solve the above-mentioned problems advantageously, and the non-aqueous secondary battery slurry of the present invention is characterized in that it contains a particulate polymer (A) and water, and the dissolved carbon dioxide concentration of the non-aqueous secondary battery slurry is 0.01 mg / ml or more and 0.08 mg / ml or less. According to the present invention, a non-aqueous secondary battery slurry can be provided that can suppress nozzle clogging and stably apply to the surface of a battery component even when an inkjet method is used.
[0019] In addition, the present invention aims to solve the above-mentioned problems advantageously, and the battery component for non-aqueous secondary batteries of the present invention is characterized in that it has a substrate and a plurality of adhesive materials in the form of dots formed on at least one side of the substrate, the substrate is a separator substrate or an electrode substrate, and the adhesive material is a dried product of the slurry for non-aqueous secondary batteries. The substrate having a plurality of adhesive materials in the form of dots formed by drying the slurry for non-aqueous secondary batteries on the surface can be firmly bonded to other adjacent battery components (such as electrodes) via the adhesive material.
[0020] Furthermore, the object of the present invention is to advantageously solve the above-mentioned problem. The manufacturing method of the battery component for non-aqueous secondary battery of the present invention is characterized in that it includes a coating step, in which the above-mentioned non-aqueous secondary battery slurry is coated on the surface of the substrate by an inkjet method, and the above-mentioned substrate is a separator substrate or an electrode substrate. According to the present invention, the non-aqueous secondary battery slurry can be stably coated on the surface of the substrate by the inkjet method, so that the adhesive material can be efficiently applied to the surface of the substrate, and as a result, the manufacturing efficiency of the battery component for secondary battery can be improved.
[0021] Furthermore, the method for manufacturing a battery member for a non-aqueous secondary battery of the present invention preferably includes a slurry degassing step before the above-mentioned coating step, in which the dissolved carbon dioxide concentration of the above-mentioned slurry for the non-aqueous secondary battery is reduced. By reducing the dissolved carbon dioxide concentration of the slurry for the non-aqueous secondary battery in the slurry degassing step, the coating property of the slurry for the non-aqueous secondary battery used in the coating step can be further improved.
[0022] In addition, the manufacturing method of the battery component for non-aqueous secondary batteries of the present invention preferably uses a substrate manufacturing device having at least a supply tank for supplying non-aqueous secondary battery slurry to an inkjet head, a degassing module for reducing the dissolved carbon dioxide concentration of the non-aqueous secondary battery slurry, and an inkjet head for ejecting the non-aqueous secondary battery slurry, and the non-aqueous secondary battery slurry is circulated in the order of the supply tank, the degassing module, and the inkjet head. By using a substrate manufacturing device having at least a supply tank, a degassing module, and an inkjet head, and circulating the non-aqueous secondary battery slurry in the order of the supply tank, the degassing module, and the inkjet head, it is possible to suppress the increase in the dissolved carbon dioxide concentration of the non-aqueous secondary battery slurry and prevent the reduction in the coating property of the non-aqueous secondary battery slurry.
[0023] Furthermore, the present invention aims to advantageously solve the above-mentioned problems, and the non-aqueous secondary battery of the present invention is characterized in that it has the above-mentioned battery component for non-aqueous secondary battery. If the non-aqueous secondary battery is a non-aqueous secondary battery having the battery component for non-aqueous secondary battery of the present invention, a non-aqueous secondary battery in which the battery components are firmly bonded to each other can be provided.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a non-aqueous secondary battery slurry that can be stably applied to a battery member surface while suppressing nozzle clogging even when an inkjet method is used, and a method for producing the same.
[0026] Furthermore, according to the present invention, it is possible to provide a battery member for a non-aqueous secondary battery that can be firmly bonded to other adjacent battery members, and a method for manufacturing the same.
[0027] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery in which battery components are firmly bonded to each other. DETAILED DESCRIPTION
[0028] Hereinafter, embodiments of the present invention will be described in detail.
[0029] Here, the non-aqueous secondary battery slurry of the present invention (hereinafter sometimes referred to as "secondary battery slurry") can be used when an adhesive material for bonding battery components to each other is formed on the surface of the battery component. Specifically, the non-aqueous secondary battery slurry of the present invention can be used for the manufacture of the battery component for the non-aqueous secondary battery of the present invention and the non-aqueous secondary battery. Moreover, the non-aqueous secondary battery slurry of the present invention can be obtained by the manufacturing method of the non-aqueous secondary battery slurry of the present invention.
[0030] (Method for producing slurry for non-aqueous secondary battery)
[0031] The method for producing a secondary battery slurry of the present invention includes a degassing step of reducing the dissolved carbon dioxide concentration of a mixture containing a particulate polymer (A) and water and optionally further containing a particulate polymer (B) described below and other components.
[0032] <Particle-like polymer (A)>
[0033] Here, the particulate polymer (A) is a component that functions as a binder in an adhesive material for bonding battery components such as separators and electrodes to each other. By using the particulate polymer (A) as a binder, battery components can be firmly bonded to each other via the binder.
[0034] [composition]
[0035] Monomers for preparing the granular polymer (A) include, for example, vinyl chloride monomers such as vinyl chloride and vinylidene chloride; vinyl acetate monomers such as vinyl acetate; aromatic vinyl monomers such as styrene, α-methylstyrene, butoxystyrene, and vinylnaphthalene; vinylamine monomers such as vinylamine; vinylamide monomers such as N-vinylformamide and N-vinylacetamide; (meth)acrylate monomers such as methyl acrylate, ethyl acrylate, and n-butyl acrylate; butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and cyclohexyl methacrylate; (meth)acrylamide monomers such as acrylamide and methacrylamide; (meth)acrylonitrile monomers such as acrylonitrile and methacrylonitrile; fluorine-containing (meth)acrylate monomers such as 2-(perfluorohexyl)ethyl methacrylate and 2-(perfluorobutyl)ethyl acrylate; maleimide; maleimide derivatives such as phenylmaleimide, etc. These monomers may be used alone or in combination of two or more at any ratio. Furthermore, as the monomer for preparing the particulate polymer (A), an acid group-containing monomer, a hydroxyl group-containing monomer, and a crosslinking monomer described in detail later can also be used.
[0036] In the present invention, (meth)acrylic acid means acrylic acid and / or methacrylic acid, and (meth)acrylonitrile means acrylonitrile and / or methacrylonitrile.
[0037] <<Core-Shell Structure>>
[0038] Here, as long as the granular polymer (A) is granular in water, it can be made into any particle structure, preferably having a core-shell structure having a core and a shell covering the outer surface of the core. In addition, the shell can cover the outer surface of the core as a whole, or partially cover the outer surface of the core. In addition, even if it appears that the outer surface of the core is completely covered by the shell, as long as a hole connecting the inside and outside of the shell is formed, the shell is the shell that partially covers the outer surface of the core. Therefore, for example, the granular polymer (A) having the following shell belongs to the granular polymer (A) in which the shell partially covers the outer surface of the core, and the shell has pores connected to the outer surface of the core from the outer surface of the shell (i.e., the outer peripheral surface of the granular polymer (A)).
[0039] -Core Composition-
[0040] Moreover, as the monomer for preparing the core of the granular polymer (A), the same monomer as the above-mentioned monomer can be cited. Among these, from the viewpoint of making the battery components more firmly bonded to each other via an adhesive material, it is preferred to use at least one of an aromatic vinyl monomer and a (meth) acrylic acid ester monomer, and more preferably use both an aromatic vinyl monomer and a (meth) acrylic acid ester monomer. That is, the core of the granular polymer (A) preferably includes at least one of an aromatic vinyl monomer unit and a (meth) acrylic acid ester monomer unit, and more preferably includes both an aromatic vinyl monomer unit and a (meth) acrylic acid ester monomer unit. Moreover, it is further preferred that the core of the granular polymer (A) includes a monomer unit from styrene and a monomer unit from n-butyl acrylate.
[0041] In the present invention, “containing a monomer unit” means “a polymer obtained by using the monomer contains a repeating unit derived from the monomer”.
[0042] Moreover, from the viewpoint of more firmly bonding the battery components to each other via the adhesive material, when all the repeating units (all monomer units) contained in the core portion of the granular polymer (A) are taken as 100 mass %, the proportion of the aromatic vinyl monomer units in the core portion of the granular polymer (A) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 75 mass % or more, preferably 95 mass % or less, more preferably 90 mass % or less.
[0043] In addition, from the viewpoint of further firmly bonding the battery components to each other via the adhesive material, the proportion of the (meth)acrylate monomer units in the core portion of the particulate polymer (A), when all repeating units (all monomer units) contained in the core portion of the particulate polymer (A) are taken as 100% by mass, is preferably 2% by mass or more, more preferably 3% by mass or more, further preferably 4% by mass or more, preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less.
[0044] In the present invention, the ratio of each monomer unit can be 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0045] The core of the particulate polymer (A) may contain an acid group-containing monomer unit. Examples of the acid group-containing monomer that can form the acid group-containing monomer unit include monomers having an acid group, such as monomers having a carboxylic acid group, monomers having a sulfonic acid group, and monomers having a phosphoric acid group.
[0046] Examples of the monomer having a carboxylic acid group include monocarboxylic acids and dicarboxylic acids. Examples of the monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of the dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0047] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0048] Furthermore, examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0049] In the present invention, (meth)allyl means allyl and / or methallyl, and (meth)acryloyl means acryloyl and / or methacryloyl.
[0050] Among these, as the acid group-containing monomer, a monomer having a carboxylic acid group is preferred, a monocarboxylic acid is particularly preferred, and (meth)acrylic acid is further preferred.
[0051] Furthermore, the acid group-containing monomer may be used alone or in combination of two or more at any ratio.
[0052] In addition, when the whole repeating units (whole monomeric units) included in the core of granular polymer (A) are taken as 100 mass %, the ratio of the acidic monomeric unit in the core of granular polymer (A) is preferably more than 0.1 mass %, more preferably more than 1 mass %, preferably below 15 mass %, more preferably below 10 mass %.By controlling the ratio of the acidic monomeric unit in the above-mentioned scope, when the preparation of granular polymer (A), the dispersibility of the polymer of core can be improved, it is easy to form the shell portion that partially covers the outer surface of the core at the outer surface of the polymer of core.
[0053] Furthermore, the core portion of the particulate polymer (A) may contain a hydroxyl group-containing monomer unit.
[0054] Examples of the hydroxyl-containing monomers that can form hydroxyl-containing monomer units include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, etc. These may be used alone or in combination of two or more at any ratio.
[0055] In addition, when all repeating units (all monomer units) contained in the core of the granular polymer (A) are taken as 100% by mass, the ratio of the hydroxyl-containing monomer units in the core of the granular polymer (A) is preferably 0.1% by mass or more, more preferably 1% by mass or more, preferably 15% by mass or less, more preferably 10% by mass or less. By controlling the ratio of the hydroxyl-containing monomer units within the above range, the dispersibility of the polymer in the core can be further improved during the preparation of the granular polymer (A), and it is easier to form a shell portion that partially covers the outer surface of the core of the granular polymer (A).
[0056] In addition, the core of the granular polymer (A) preferably includes a crosslinkable monomer unit in addition to the above-mentioned monomer unit. Here, the crosslinkable monomer that can form the crosslinkable monomer unit refers to a monomer that can form a crosslinked structure during or after polymerization by heating or irradiation with energy lines. By including the crosslinkable monomer unit in the granular polymer (A), the insoluble component rate of the granular polymer (A) in tetrahydrofuran (THF) described later and the electrolyte swelling degree of the granular polymer (A) described later can be easily controlled within a preferred range.
[0057] As a crosslinking monomer, for example, a multifunctional monomer having two or more polymerizable reactive groups in the crosslinking monomer can be cited. As such a multifunctional monomer, for example: divinyl monomers such as divinylbenzene, 1,3-butadiene, isoprene, and allyl methacrylate; di(meth)acrylate monomers such as ethylene dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diacrylate-1,3-butylene glycol ester; tri(meth)acrylate monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate; γ-methacryloxypropyl trimethoxysilane, etc. Among these, from the viewpoint of easily controlling the insoluble component rate of the granular polymer (A) in THF and the electrolyte swelling degree of the granular polymer (A), a di(meth)acrylate monomer is more preferred. These may be used alone or in combination of two or more at any ratio.
[0058] In addition, when all repeating units (all monomer units) contained in the core of the granular polymer (A) are taken as 100% by mass, the ratio of the crosslinkable monomer units in the core of the granular polymer (A) is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, further preferably 0.5% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. By controlling the ratio of the crosslinkable monomer units within the above range, the battery components can be further firmly bonded to each other via the adhesive material, and the insoluble component rate of the granular polymer (A) in THF and the electrolyte swelling degree of the granular polymer (A) can be controlled to improve the low temperature output characteristics of the secondary battery.
[0059] - Shell composition -
[0060] In addition, as the monomer for preparing the shell part of the granular polymer (A), for example, the same monomer as the monomer exemplified as the monomer that can be used to manufacture the core part of the granular polymer (A) can be mentioned. In addition, such monomers can be used alone or in combination of two or more in any ratio.
[0061] Among these monomers, from the viewpoint of further firmly bonding the battery components to each other via the adhesive material, as a monomer that can be used to prepare the shell portion of the granular polymer (A), it is preferred to use at least one of a (meth)acrylate monomer and an aromatic vinyl monomer, and more preferably use both (meth)acrylate monomers and aromatic vinyl monomers. That is, the shell portion of the granular polymer (A) preferably includes at least one of a (meth)acrylate monomer unit and an aromatic vinyl monomer unit, and more preferably includes both (meth)acrylate monomer units and aromatic vinyl monomer units. Moreover, it is further preferred that the shell portion of the granular polymer (A) includes monomer units from n-butyl acrylate and monomer units from styrene.
[0062] Furthermore, from the viewpoint of further firmly bonding the battery components to each other via the adhesive material, the proportion of the (meth)acrylate monomer units in the shell portion of the particulate polymer (A), when all repeating units (all monomer units) contained in the shell portion of the particulate polymer (A) are taken as 100% by mass, is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 50% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less.
[0063] In addition, from the viewpoint of further firmly bonding the battery components to each other via the adhesive material, when all the repeating units (all monomer units) contained in the shell portion of the granular polymer (A) are taken as 100 mass%, the proportion of the aromatic vinyl monomer units in the shell portion of the granular polymer (A) is preferably 5 mass% or more, more preferably 10 mass% or more, further preferably 15 mass% or more, preferably 40 mass% or less, more preferably 30 mass% or less, and further preferably 25 mass% or less.
[0064] The shell of the granular polymer (A) may also contain an acid group-containing monomer unit in addition to the (meth)acrylate monomer unit and the aromatic vinyl monomer unit. Here, as the acid group-containing monomer that can form the acid group-containing monomer unit, monomers having an acid group, such as monomers having a carboxylic acid group, monomers having a sulfonic acid group, and monomers having a phosphoric acid group can be cited. Specifically, as the acid group-containing monomer, monomers similar to the acid group-containing monomers that can be used for the formation of the core can be cited.
[0065] Among these, as the acid group-containing monomer, a monomer having a carboxylic acid group is preferred, a monocarboxylic acid is particularly preferred, and (meth)acrylic acid is further preferred.
[0066] Furthermore, the acid group-containing monomer may be used alone or in combination of two or more at any ratio.
[0067] Moreover, when all repeating units (all monomer units) contained in the shell portion of the particulate polymer (A) are taken as 100 mass %, the proportion of the acid group-containing monomer units in the shell portion of the particulate polymer (A) is preferably 0.1 mass % or more, more preferably 0.4 mass % or more, further preferably 0.7 mass % or more, preferably 15 mass % or less, more preferably 10 mass % or less, further preferably 5 mass % or less.
[0068] By controlling the ratio of the acid group-containing monomer unit to fall within the above range, the dispersibility of the particulate polymer (A) can be improved, and the battery members can be more firmly bonded to each other via the adhesive.
[0069] Here, the shell portion of the particulate polymer (A) may contain a hydroxyl group-containing monomer unit.
[0070] Examples of the hydroxyl group-containing monomers that can form the hydroxyl group-containing monomer units in the shell portion of the particulate polymer (A) include the same hydroxyl group-containing monomers that can be used for forming the core portion of the particulate polymer (A).
[0071] Moreover, when all repeating units (all monomer units) contained in the shell of the particulate polymer (A) are taken as 100% by mass, the proportion of the hydroxyl-containing monomer units in the shell of the particulate polymer (A) is preferably 0.1% by mass or more, more preferably 0.4% by mass or more, further preferably 0.7% by mass or more, preferably 15% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less. By controlling the proportion of the hydroxyl-containing monomer units within the above range, the dispersibility of the particulate polymer (A) can be improved, and the battery components can be further firmly bonded to each other via the adhesive material.
[0072] In addition, the shell of the granular polymer (A) may include a crosslinkable monomer unit. Here, as a crosslinkable monomer that can form a crosslinkable monomer unit, for example, the same monomer as the monomer exemplified as a crosslinkable monomer that can be used for the formation of the core of the granular polymer (A) can be cited. Among these, di(methyl)acrylate monomers and divinyl monomers are preferred, and for example, allyl methacrylate is preferred. In addition, the crosslinkable monomer can be used alone or in combination of two or more in any ratio.
[0073] Moreover, when all repeating units (all monomer units) contained in the shell portion of the particulate polymer (A) are taken as 100% by mass, the proportion of the crosslinkable monomer units in the shell portion of the particulate polymer (A) is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, further preferably 0.2% by mass or more, preferably 4% by mass or less, more preferably 3% by mass or less, further preferably 2% by mass or less.
[0074] In addition, as long as the desired effect is not significantly impaired, the granular polymer (A) can also have any constituent elements except the above-mentioned core and shell. Specifically, for example, the granular polymer (A) can have a part formed by a polymer different from the core inside the core. When giving a specific example, the seed particles used in the case of manufacturing the granular polymer (A) by the seed polymerization method can remain inside the core. However, from the viewpoint of significantly playing the desired effect, the granular polymer (A) preferably only has a core and a shell.
[0075] [Glass transition temperature]
[0076] The glass transition temperature of the particulate polymer (A) is preferably -50°C or higher, more preferably -20°C or higher, further preferably 0°C or higher, preferably 200°C or lower, more preferably 150°C or lower, further preferably 110°C or lower. If the glass transition temperature of the particulate polymer (A) is -50°C or higher, the battery components can be more firmly bonded to each other via the adhesive. On the other hand, if the glass transition temperature of the particulate polymer (A) is 200°C or lower, the polymerization stability of the particulate polymer (A) can be ensured.
[0077] The glass transition temperature of the particulate polymer (A) can be adjusted by, for example, changing the type and ratio of monomers used in the preparation of the particulate polymer (A).
[0078] -Glass transition temperature of the core-
[0079] When the particulate polymer (A) has a core-shell structure, the preferred range of the glass transition temperature of the core polymer can be the same range as the glass transition temperature of the particulate polymer (A) described above.
[0080] The glass transition temperature of the core portion of the particulate polymer (A) can be adjusted by, for example, changing the type and ratio of monomers used for preparing the core portion of the particulate polymer (A).
[0081] - Glass transition temperature of the shell -
[0082] Furthermore, when the particulate polymer (A) has a core-shell structure, the glass transition temperature of the shell portion of the particulate polymer (A) is preferably -50°C or higher, more preferably -45°C or higher, further preferably -40°C or higher, preferably 60°C or lower, more preferably 50°C or lower, further preferably 40°C or lower. If the glass transition temperature of the shell portion of the particulate polymer (A) is -50°C or higher, the low-temperature output characteristics of the secondary battery can be further improved. On the other hand, if the glass transition temperature of the shell portion of the particulate polymer (A) is 60°C or lower, the battery components can be more firmly bonded to each other via the adhesive material.
[0083] The glass transition temperature of the shell portion of the particulate polymer (A) can be adjusted by, for example, changing the type and ratio of monomers used for preparing the shell portion of the particulate polymer (A).
[0084] Furthermore, from the viewpoint of further firmly bonding the battery components to each other via the adhesive material, the glass transition temperature of the shell portion of the granular polymer (A) is preferably 10°C or more lower than the glass transition temperature of the core portion of the above-mentioned granular polymer (A), more preferably 30°C or more lower than the glass transition temperature of the core portion of the above-mentioned granular polymer (A), further preferably 50°C or more lower than the glass transition temperature of the core portion of the above-mentioned granular polymer (A), and most preferably 100°C or more lower than the glass transition temperature of the core portion of the above-mentioned granular polymer (A).
[0085] [Insoluble component ratio]
[0086] Moreover, the insoluble component rate of the granular polymer (A) in tetrahydrofuran (THF) is preferably 80% by mass or more, more preferably 82% by mass or more, further preferably 85% by mass or more, preferably 99% by mass or less, more preferably 95% by mass or less, and further preferably 90% by mass or less. If the insoluble component rate of the granular polymer (A) in THF is 80% by mass or more, the low temperature output characteristics of the secondary battery can be further improved. On the other hand, if the insoluble component rate of the granular polymer (A) in THF is 99% by mass or less, the battery components can be further firmly bonded to each other via the adhesive material.
[0087] In the present invention, the "ratio of insoluble components in THF" can be measured using the measurement method described in Examples of the present specification.
[0088] The insoluble content of the particulate polymer (A) in THF can be adjusted by, for example, changing the type and ratio of the monomers used in the preparation of the particulate polymer (A).
[0089] [Volume average particle size]
[0090] In addition, the volume average particle size of the granular polymer (A) is preferably 100 nm or more, more preferably 200 nm or more, further preferably 300 nm or more, preferably 1000 nm or less, more preferably 700 nm or less, and further preferably 500 nm or less. If the volume average particle size of the granular polymer (A) is 100 nm or more, the battery components can be further firmly bonded to each other via the adhesive. On the other hand, if the volume average particle size of the granular polymer (A) is 1000 nm or less, the clogging of the nozzle in the case of the inkjet method can be further suppressed, and the adhesive can be more efficiently applied to the surface of the battery component.
[0091] In the present invention, the “volume average particle size” refers to the particle size at which the cumulative volume calculated from the small particle size side is 50% in a volume-based particle size distribution measured using a laser diffraction method. The “volume average particle size” can be measured using the measurement method described in Examples of this specification.
[0092] The volume average particle size of the particulate polymer (A) can be adjusted by, for example, changing the type and amount of the polymerization initiator and emulsifier used in the preparation of the particulate polymer (A).
[0093] [Electrolyte swelling degree]
[0094] Moreover, the electrolyte swelling degree of the granular polymer (A) is preferably 1.01 times or more, more preferably 1.1 times or more, further preferably 1.2 times or more, preferably 20 times or less, more preferably 15 times or less, further preferably 10 times or less. If the electrolyte swelling degree of the granular polymer (A) is preferably 1.01 times or more, the battery components can be further firmly bonded to each other (especially in the electrolyte) via the adhesive material. On the other hand, if the electrolyte swelling degree of the granular polymer (A) is 20 times or less, the low-temperature output characteristics of the secondary battery can be further improved.
[0095] In the present invention, the "electrolyte swelling degree" can be measured using the measurement method described in the Examples of this specification.
[0096] The degree of swelling of the particulate polymer (A) with respect to the electrolyte solution can be adjusted by, for example, changing the type and ratio of monomers used in the preparation of the particulate polymer (A).
[0097] <<Method for preparing granular polymer (A)>>
[0098] Moreover, the granular polymer (A) can be prepared by polymerizing the above-mentioned monomers. Here, as a polymerization method, any one of emulsion polymerization, suspension polymerization, bulk polymerization and solution polymerization can be used, wherein emulsion polymerization is preferably used. Moreover, the granular polymer (A) having the above-mentioned core-shell structure can be prepared by, for example, the following method, that is, using a monomer forming the core of the granular polymer (A) and a monomer forming the shell of the granular polymer (A), changing the ratio of these monomers over time, thereby polymerizing in stages. Specifically, the granular polymer (A) having a core-shell structure can be manufactured by a continuous multi-stage emulsion polymerization method and a multi-stage suspension polymerization method in which the polymer in the later stage is sequentially coated with the polymer in the previous stage.
[0099] Therefore, an example of the case where the above-mentioned particulate polymer (A) having a core-shell structure is obtained by a multi-stage emulsion polymerization method is shown below.
[0100] During polymerization, according to conventional methods, as emulsifiers, anionic surfactants such as sodium dodecylbenzenesulfonate and sodium dodecyl sulfate, nonionic surfactants such as polyoxyethylene nonylphenyl ether and sorbitan monolaurate, or cationic surfactants such as octadecylamine acetate can be used. In addition, as polymerization initiators, peroxides such as tert-butyl peroxy-2-ethylhexanoate, potassium persulfate, and cumene peroxide can be used; azo compounds such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) and 2,2'-azobis(2-amidinopropane) hydrochloride can be used.
[0101] In addition, as the polymerization step, first, a monomer forming the core of the granular polymer (A) and an emulsifier are mixed and emulsion polymerization is performed at once, thereby obtaining a granular polymer constituting the core of the granular polymer (A). Furthermore, in the presence of the granular polymer constituting the core of the granular polymer (A), a monomer forming the shell of the granular polymer (A) is polymerized, thereby obtaining the granular polymer (A) having the core-shell structure.
[0102] Furthermore, when preparing a granular polymer (A) in which the shell part partially covers the outer surface of the core part, the monomer forming the shell part of the granular polymer (A) is preferably supplied to the polymerization system in batches or continuously. By supplying the monomer forming the shell part of the granular polymer (A) to the polymerization system in batches or continuously, the polymer constituting the shell part of the granular polymer (A) can be made into particles, and the particles are combined with the core part to form a shell part that partially covers the core part.
[0103] <Water>
[0104] The water used in the method for producing a secondary battery slurry of the present invention is a component that functions as a dispersion medium for dispersing the particulate polymer (A). The water is not particularly limited as long as it can disperse the particulate polymer (A).
[0105] Moreover, in the method for producing a secondary battery slurry of the present invention, the amount of water used is preferably 230 parts by mass or more, more preferably 390 parts by mass or more, further preferably 900 parts by mass or more, preferably 9900 parts by mass or less, more preferably 3300 parts by mass or less, and further preferably 1900 parts by mass or less, relative to 100 parts by mass of the granular polymer (A). If the amount of water used is above the above lower limit, when the secondary battery slurry is applied by an inkjet method, clogging of the nozzle can be further suppressed.
[0106] <Particle-like polymer (B)>
[0107] Moreover, as a granular polymer (B) that can be used arbitrarily in the method for manufacturing the slurry for non-aqueous secondary batteries of the present invention, it is not particularly limited as long as it is a granular polymer different from the granular polymer (A). The granular polymer (B) is a component that is expected to act as a bonding material in a bonding material that bonds the granular polymer (A) to each other. By using a granular polymer (B) as a bonding material, the granular polymer (A) can be firmly bonded to each other, and then the battery components can be firmly bonded to each other via a bonding material. As a polymer forming a granular polymer (B), for example: fluorine-based polymers such as polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP) copolymers; conjugated diene polymers such as styrene-butadiene copolymers (SBR), acrylonitrile-butadiene copolymers (NBR); hydrogenated products of conjugated diene polymers; polymers (acrylic polymers) containing (meth) alkyl acrylate monomer units. The particulate polymer (B) may be used alone or in combination of two or more at any ratio.
[0108] In the method for producing secondary battery slurry of the present invention, since the dissolved carbon dioxide concentration of the mixture is reduced, even when the particulate polymer (B) is used in combination in the method for producing secondary battery slurry, clogging of the nozzle can be suppressed when the secondary battery slurry is applied by the inkjet method.
[0109] Here, the glass transition temperature of the particulate polymer (B) is preferably -40°C or higher, more preferably -30°C or higher, further preferably -20°C or higher, preferably 20°C or lower, more preferably 15°C or lower, further preferably 10°C or lower. If the glass transition temperature of the particulate polymer (B) is -40°C or higher, the low-temperature output characteristics of the secondary battery can be further improved, and if the glass transition temperature of the particulate polymer (B) is 20°C or lower, the powdering resistance of the adhesive material can be improved.
[0110] [Volume average particle size]
[0111] In addition, the volume average particle size of the granular polymer (B) is preferably 100 nm or more, more preferably 200 nm or more, further preferably 300 nm or more, preferably 1000 nm or less, more preferably 700 nm or less, further preferably 500 nm or less. If the volume average particle size of the granular polymer (B) is 100 nm or more, the granular polymer (B) can fully exert the desired characteristics. In addition, if the volume average particle size of the granular polymer (B) is 1000 nm or less, even in the case of an inkjet method, the clogging of the nozzle caused by the granular polymer (B) can be fully suppressed.
[0112] The volume average particle size of the particulate polymer (B) can be adjusted by, for example, changing the type and amount of the polymerization initiator and emulsifier used in the preparation of the particulate polymer (B).
[0113] Moreover, relative to 100 parts by mass of the granular polymer (A), the amount of the granular polymer (B) is preferably more than 1 part by mass, more preferably more than 5 parts by mass, more preferably more than 10 parts by mass, preferably less than 30 parts by mass, more preferably less than 25 parts by mass, and more preferably less than 20 parts by mass. If the amount of the granular polymer (B) is more than the above lower limit, the anti-powdering property of the adhesive material formed by the secondary battery slurry of the present invention can be further improved. In addition, if the amount of the granular polymer (B) is less than the above upper limit, the low temperature output characteristics can be further improved.
[0114] <<Method for preparing granular polymer (B)>>
[0115] The particulate polymer (B) can be prepared by, for example, emulsion polymerization of a monomer mixture containing monomers that can constitute the particulate polymer (B). The emulsion polymerization method is not particularly limited, and a conventionally known emulsion polymerization method can be used.
[0116] <Other ingredients>
[0117] Furthermore, other components that can be used arbitrarily in the method for producing the secondary battery slurry of the present invention are not particularly limited as long as they are components other than the above-mentioned particulate polymer (A), particulate polymer (B) and water. Examples of such components include polyol compounds and additives.
[0118] <Polyol Compound>
[0119] The polyol compound is a compound having more than two hydroxyl groups (-OH) in one molecule. Moreover, by including the polyol compound in the secondary battery slurry of the present invention, the clogging of the nozzle can be further suppressed when the secondary battery slurry is applied to the surface of the battery component by an inkjet method, and the adhesive material can be further efficiently applied to the surface of the battery component. As such, the reason why the clogging of the nozzle can be suppressed when the secondary battery slurry is applied by an inkjet method by including the polyol compound is not yet clear, but it is considered to be the following reason. It can be considered that this is because: by the polyol compound having multiple hydroxyl groups in one molecule acting as a wetting agent, it is possible to suppress the vaporization of water in the secondary battery slurry in the nozzle (especially the vaporization of water in the nozzle during the placement period when the coating is temporarily interrupted), and as a result, the precipitation of the particulate polymer (A) etc. can be suppressed.
[0120] Here, as a polyol compound, for example, propylene glycol, ethylene glycol, glycerol, 1,3-propylene glycol, 1,4-butylene glycol, glucose, fructose, cellulose, etc. can be cited. These can be used alone or in combination of two or more in any ratio. Moreover, among these, from the viewpoint of further suppressing the clogging of the nozzle when applying the non-aqueous secondary battery slurry by inkjet method and further efficiently imparting the adhesive material to the surface of the battery component, propylene glycol, ethylene glycol, glycerol, 1,3-propylene glycol, 1,4-butylene glycol are preferred, and propylene glycol, ethylene glycol, and glycerol are more preferred.
[0121] Moreover, the amount of the polyol compound used is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, further preferably 30 parts by mass or more, preferably 400 parts by mass or less, more preferably 300 parts by mass or less, further preferably 200 parts by mass or less, relative to 100 parts by mass of the particulate polymer (A). If the amount of the polyol compound used is within the above range, it is possible to fully suppress nozzle clogging when applying the slurry for non-aqueous secondary batteries by an inkjet method.
[0122] <<Additives>>
[0123] In addition, there are no particular restrictions on the additives that can be used in the method for manufacturing the secondary battery slurry of the present invention, and examples thereof include surface tension modifiers, dispersants, viscosity modifiers, reinforcing materials, electrolyte additives, etc. These are not particularly limited as long as they do not affect the battery reaction, and known additives can be used, such as additives described in International Publication No. 2012 / 115096. In addition, these additives can be used alone, or two or more can be used in combination at any ratio.
[0124] <Degassing process>
[0125] Moreover, in the manufacturing method of the secondary battery slurry of the present invention, in the degassing process, the dissolved carbon dioxide concentration of the mixture containing the above-mentioned components is reduced. Thus, even in the case of using an inkjet method, a secondary battery slurry that can suppress nozzle clogging and can be stably coated on the surface of a battery component can be obtained compared to the case where the mixture is directly used without degassing. In addition, in the present invention, dissolved carbon dioxide refers to carbon dioxide dissolved in the secondary battery slurry.
[0126] The reason why the coating properties of the secondary battery slurry obtained by the production method of the present invention are stable is not yet clear, but it is speculated that by reducing the dissolved carbon dioxide concentration in the above-mentioned mixture, the dispersibility of the particulate polymer (A) in the mixture is stabilized and the aggregation of the particulate polymer (A) is suppressed.
[0127] Here, the carbon dioxide concentration of the mixture is usually 0.1 mg / ml or more.
[0128] Moreover, degassing is performed in the degassing process until the dissolved carbon dioxide concentration of the above-mentioned mixture is preferably more than 0.01mg / ml, more preferably more than 0.02mg / ml, preferably less than 0.08mg / ml, more preferably less than 0.06mg / ml. By the dissolved carbon dioxide concentration of the mixture being more than the above-mentioned lower limit, the coagulation of the granular polymer (A) can be suppressed. Moreover, if degassing is performed until the dissolved carbon dioxide concentration of the mixture is within the above-mentioned range, a secondary battery slurry with further improved coating properties can be obtained. In addition, in the case where the secondary battery slurry includes the above-mentioned granular polymer (B), if degassing is performed until the dissolved carbon dioxide concentration of the above-mentioned mixture is more than the above-mentioned lower limit, the coagulation of the granular polymer caused by the adsorption of the granular polymer (B) on the granular polymer (A) can be suppressed.
[0129] In addition, in the present invention, the "dissolved carbon dioxide concentration" of the slurry for secondary batteries can be measured using the measurement method described in Examples of this specification.
[0130] Here, the mixing can be performed using a common stirring container, ball mill, sand mill, bead mill, pigment disperser, ultrasonic disperser, grinding stirrer, homogenizer, planetary mixer, filmix, etc. The mixing conditions are not particularly limited, and the mixing can usually be performed at room temperature (25° C.) to 80° C. for 10 minutes to several hours.
[0131] The method for degassing the mixture is not particularly limited as long as the dissolved carbon dioxide concentration of the mixture can be reduced, and known degassing methods such as heating degassing, reduced pressure degassing, and degassing by adding a defoaming agent can be used.
[0132] Moreover, in the case of heating degassing, the mixture is usually heated and left to stand at normal pressure (1 atm) preferably at 30°C or more, more preferably at 35°C or more, preferably at 50°C or less, and more preferably at 40°C or less. If the heating temperature is above the lower limit, the dissolved carbon dioxide concentration of the mixture can be easily adjusted to within the above range. In addition, if the heating temperature is below the upper limit, the components in the secondary battery slurry such as the particulate polymer (A) can be inhibited from being affected by heat and deteriorating.
[0133] In addition, the standing time during heating degassing is usually more than 1 hour, preferably more than 6 hours, more preferably more than 12 hours, preferably less than 30 hours, more preferably less than 24 hours. If the standing time is more than the above-mentioned lower limit, the dissolved carbon dioxide concentration of the mixture can be more easily adjusted to within the above-mentioned range. In addition, if the standing time is below the above-mentioned upper limit, the time required for manufacturing secondary battery slurry can be shortened and manufacturing efficiency can be improved.
[0134] When degassing is performed under reduced pressure, the mixture is usually depressurized to preferably about 1.0 kPa to 0.5 kPa at room temperature (25° C.), and the depressurized state is maintained while stirring until bubbles are no longer generated.
[0135] Furthermore, when deaeration is performed by adding a defoaming agent, the type of the defoaming agent is not particularly limited, and a conventionally known defoaming agent can be used. In addition, the amount of the defoaming agent added is not particularly limited, and may be appropriately set.
[0136] The storage of the secondary battery slurry obtained by degassing the mixture is not particularly limited, but it is preferably stored in a container that can prevent the dissolution of carbon dioxide.
[0137] <Slurry for non-aqueous secondary batteries>
[0138] Moreover, the secondary battery slurry of the present invention manufactured by the above-mentioned manufacturing method comprises the above-mentioned granular polymer (A), water, and optionally comprises the above-mentioned granular polymer (B) and / or other components, and the dissolved carbon dioxide concentration is 0.01 mg / ml or more, preferably 0.02 mg / ml or more, 0.08 mg / ml or less, preferably 0.06 mg / ml or less. According to the secondary battery slurry of the present invention, it is possible to provide a secondary battery slurry that can effectively suppress the clogging of the nozzle and has sufficiently stable coating properties even when an inkjet method is adopted. That is, if the secondary battery slurry of the present invention is used, the surface of the battery component can be efficiently given an adhesive material. Furthermore, if the secondary battery slurry of the present invention is used to give an adhesive material to the surface of the battery component, the battery components can be firmly bonded to each other via the adhesive material.
[0139] Here, the total solid content concentration of the secondary battery slurry is not particularly limited, preferably 1% by mass or more, more preferably 3% by mass or more, preferably 30% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less. If the total solid content concentration of the secondary battery slurry is within the above range, the secondary battery slurry of the present invention can be used to efficiently manufacture a secondary battery battery component.
[0140] Moreover, in the secondary battery slurry, the content of the particulate polymer (A) is not particularly limited. When the total solid content in the secondary battery slurry is taken as 100% by mass, the content of the particulate polymer (A) is preferably 70% by mass or more, more preferably 80% by mass or more, preferably 95% by mass or less, and more preferably 90% by mass or less. If the content of the particulate polymer (A) in the secondary battery slurry is above the above lower limit, sufficient adhesion of the particulate polymer (A) can be obtained. In addition, if the content of the particulate polymer (A) in the secondary battery slurry is below the above upper limit, the coating property of the secondary battery slurry is stable.
[0141] In addition, in the secondary battery slurry, the water content is not particularly limited, and relative to 100 parts by mass of the particulate polymer (A), it is preferably 230 parts by mass or more, more preferably 390 parts by mass or more, further preferably 900 parts by mass or more, preferably 9900 parts by mass or less, more preferably 3300 parts by mass or less, and further preferably 1900 parts by mass or less. If the water content in the secondary battery slurry is above the above lower limit, when the secondary battery slurry is applied by inkjet method, the clogging of the nozzle can be further suppressed. In addition, if the water content in the secondary battery slurry is below the above upper limit, the water contained in the secondary battery slurry will not be excessively difficult to vaporize, and the drying efficiency of the secondary battery slurry can be fully ensured.
[0142] Furthermore, in the secondary battery slurry, the content of the particulate polymer (B) is not particularly limited, and relative to 100 parts by mass of the particulate polymer (A), it is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and further preferably 20 parts by mass or less. If the content of the particulate polymer (B) in the secondary battery slurry is above the above lower limit, the powder loss resistance of the adhesive material formed by the secondary battery slurry of the present invention can be improved. In addition, if the content of the particulate polymer (B) in the secondary battery slurry is below the above upper limit, the low temperature output characteristics can be further improved.
[0143] Moreover, the content of coarse particles with a diameter of 10 μm or more in the secondary battery slurry of the present invention is preferably 100 ppm or less, more preferably 50 ppm or less, and further preferably 10 ppm or less. If the content of coarse particles with a diameter of 10 μm or more is 100 ppm or less, the battery components can be further firmly bonded to each other via the adhesive material. In addition, the coarse particles contained in the secondary battery slurry are usually formed by a granular polymer (A) and / or a granular polymer (B).
[0144] In the present invention, "the content of coarse particles" can be measured by the following procedure.
[0145] -Determination of the content of coarse particles-
[0146] Measure the mass (B) of a nylon mesh with an average pore size of 10 μm and place it in a funnel. Pour 100 g of secondary battery slurry into it and filter it. Next, pour in ion exchange water and wash until the captured material on the nylon mesh is no longer turbid, and dry it in an oven at 90°C for more than 60 minutes. After leaving it to cool, measure the mass (A) of the nylon mesh and measure the amount of mesh residue. Then, calculate the amount of mesh residue, that is, the amount of coarse particles with a particle size of 10 μm or more in the slurry, according to the following formula.
[0147] Content of coarse particles (ppm) = (AB) / (C×D / 100)×1000000
[0148] A: Mass of net + dried material (g)
[0149] B: Mass of the net (g)
[0150] C: Mass of filtered slurry (g)
[0151] D: Total solid content concentration of slurry (%)
[0152] (Battery member for non-aqueous secondary battery)
[0153] The battery component for a non-aqueous secondary battery of the present invention (hereinafter sometimes referred to as "battery component for a secondary battery") comprises a substrate and a plurality of adhesive materials in the form of dots formed on at least one side of the substrate, wherein the substrate is a separator substrate or an electrode substrate, and the adhesive material is a dried product of the slurry for a non-aqueous secondary battery of the present invention.
[0154] When the substrate is a separator substrate, the battery member for a secondary battery of the present invention can be used as a separator for a secondary battery, and when the substrate is an electrode substrate, the battery member for a secondary battery of the present invention can be used as an electrode for a secondary battery.
[0155] Here, a substrate having a plurality of adhesive materials in the form of dots which are the dried product of the slurry for secondary batteries of the present invention on at least one side is bonded to other battery components (e.g., electrodes) by bonding the surface on which the adhesive material is formed (or to be formed) (hereinafter referred to as the "formed surface"), thereby being firmly bonded to the other battery components.
[0156] <Spacer Base Material>
[0157] The separator substrate is not particularly limited, and a known separator substrate can be used. In addition, the separator substrate may have a porous membrane layer formed on one or both sides.
[0158] In addition, as spacer substrate and porous film layer, it is not particularly limited, and any spacer substrate and porous film layer that can be used in the field of secondary batteries, such as spacer substrate and porous film layer recorded in Japanese Patent Publication No. 2012-204303 and Japanese Patent Publication No. 2013-145763, can be used.Here, porous film layer refers to a layer comprising non-conductive particles such as recorded in Japanese Patent Publication No. 2013-145763.
[0159] <Electrode Base Material>
[0160] In addition, as electrode substrate, it is not particularly limited, and known electrode substrate can be used. For example, as electrode substrate, an electrode formed by an electrode substrate formed by forming an electrode composite material layer on one or both sides of a current collector or an electrode formed by further forming a porous film layer on the electrode composite material layer of the electrode substrate can be used.
[0161] The current collector, electrode composite material layer, and porous membrane layer are not particularly limited, and any current collector, electrode composite material layer, and porous membrane layer that can be used in the field of secondary batteries, such as those described in Japanese Patent Application Laid-Open No. 2013-145763, can be used.
[0162] <Adhesive Materials>
[0163] As described above, the adhesive material formed on at least one side of the above-mentioned substrate is a dried product of the secondary battery slurry of the present invention. That is, the dried product at least contains a polymer from the above-mentioned granular polymer (A), and may arbitrarily contain a polymer and / or other components from the above-mentioned granular polymer (B). Furthermore, the dried product may also contain residual polyol compounds and water that are not vaporized by drying, and the moisture content of the adhesive material is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and most preferably 0% by mass (below the detection limit).
[0164] Furthermore, the adhesive material in a dot shape may be formed uniformly over the entire surface of the formation, or may be arranged in a predetermined pattern such as stripes, dots, or a grid in a plan view.
[0165] In addition, the cross-sectional shape of the adhesive material is not particularly limited, and can be a convex shape, a concave shape, or a concave shape, wherein, from the viewpoint of further firmly bonding the substrate to the adjacent battery member (e.g., electrode) via the adhesive material, a concave-convex shape is preferred. In addition, the cross-sectional shape of the adhesive material can be changed by, for example, adjusting the drying conditions when the adhesive material is formed using the secondary battery slurry of the present invention.
[0166] Furthermore, the amount of adhesive material formed is preferably 0.1 g / m 2 Above and 100g / m 2 Below, more preferably 0.1g / m 2 Above and 50g / m 2 Below, more preferably 0.1 g / m 2 Above and 10g / m 2 Below, particularly preferably 0.1 g / m 2 Above 1g / m 2 If the amount of adhesive material formed is 0.1g / m 2 If the amount of adhesive material formed is 100 g / m 2 Next, the battery member for secondary battery can be manufactured efficiently.
[0167] In the present invention, “the amount of adhesive material formed” refers to the amount of adhesive material formed per unit area of the forming surface, and can be calculated by dividing the mass of the adhesive material formed on the forming surface by the area of the forming surface on which the adhesive material is formed.
[0168] Here, when the formation surface is a formation surface on which the adhesive material is formed in dots at one or more places, preferably at two or more places, the size (area) of one dot formed on the formation surface is preferably 25 μm. 2 More preferably 50 μm 2 More preferably, 100 μm 2 Above, preferably 250000 μm 2 Below, more preferably 200000 μm 2 Below, more preferably 100000 μm 2 If the size of one dot is 25 μm 2 In this way, the substrate and the adjacent battery components (e.g., electrodes) can be more firmly bonded via the adhesive material. 2 Next, the battery member for secondary battery can be manufactured efficiently.
[0169] In addition, the size (area) of one point formed on the above-mentioned formation surface can be adjusted by changing the amount, shape and range of the secondary battery slurry supplied to the formation surface of the present invention. Specifically, when, for example, a bonding material is formed by an inkjet method using the secondary battery slurry of the present invention, the formation area can be adjusted by changing the frequency of the secondary battery slurry ejected from the nozzle of the inkjet head (the number of times ejected at the same point).
[0170] (Method for producing battery member for non-aqueous secondary battery)
[0171] The method for producing a battery member for a secondary battery of the present invention includes a coating step in which the slurry for a secondary battery of the present invention is coated on the surface of the substrate, which is the separator substrate or the electrode substrate, by an inkjet method.
[0172] Here, the method for producing a battery member for a secondary battery of the present invention may further include, before the coating step, a slurry degassing step of reducing the dissolved carbon dioxide concentration of the slurry for a secondary battery of the present invention.
[0173] Then, by drying the secondary battery slurry coated on the substrate surface, the battery member of the present invention can be obtained. In addition, the coating conditions and drying conditions of the secondary battery slurry can be appropriately adjusted according to the plane view shape, cross-sectional shape, formation amount and formation area of each place of the desired adhesive material.
[0174] <Slurry Degassing Process>
[0175] Moreover, in the slurry degassing process that can be arbitrarily included in the manufacturing method of the battery component for secondary batteries of the present invention, the dissolved carbon dioxide concentration of the secondary battery slurry used in the subsequent coating process is reduced. In the slurry degassing process, degassing is performed until the dissolved carbon dioxide concentration of the secondary battery slurry is preferably more than 0.01mg / ml, more preferably more than 0.02mg / ml, preferably less than 0.08mg / ml, and more preferably less than 0.06mg / ml. Thus, the reduction of the coating property of the secondary battery slurry used in the coating process can be suppressed. In addition, the degassing method of the secondary battery slurry in the slurry degassing process is not particularly limited, and the degassing method cited as a method for degassing a mixture in the manufacturing method of the secondary battery slurry of the present invention can be used.
[0176] <Coating process>
[0177] In the coating step, the slurry for secondary batteries of the present invention is coated on the surface of the substrate by an inkjet method. The slurry for secondary batteries of the present invention can be coated on the surface of the substrate in a dotted form, for example.
[0178] Here, the manufacturing method of the battery component for secondary battery of the present invention is preferably manufactured using a substrate manufacturing device having at least a supply tank for supplying non-aqueous secondary battery slurry to an inkjet head, a degassing module for reducing the dissolved carbon dioxide concentration of the non-aqueous secondary battery slurry, and an inkjet head for ejecting non-aqueous secondary battery slurry. Moreover, in the substrate manufacturing device, the non-aqueous secondary battery slurry is preferably circulated in the order of a supply tank, a degassing module, and an inkjet head. That is, the secondary battery slurry that is not ejected from the inkjet head is preferably circulated to the supply tank. By using a substrate manufacturing device having at least a supply tank, a degassing module, and an inkjet head like this, and the non-aqueous secondary battery slurry is circulated in the order of a supply tank, a degassing module, and an inkjet head, the manufacturing efficiency of the battery component for secondary battery can be improved.
[0179] (Non-aqueous secondary battery)
[0180] The secondary battery of the present invention comprises the nonaqueous secondary battery battery member of the present invention described above. Specifically, the secondary battery of the present invention comprises the nonaqueous secondary battery battery member of the present invention as at least one of a secondary battery separator and a secondary battery electrode.
[0181] <Electrode>
[0182] As the electrode used for the secondary battery of the present invention, the battery member for the secondary battery of the present invention described above may be used, or a known electrode may be used.
[0183] <Electrolyte>
[0184] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is generally used. In the case where, for example, the secondary battery is a lithium ion secondary battery, a lithium salt can be used as the supporting electrolyte. As the lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, because they are easily soluble in solvents and show a high degree of dissociation, LiPF6, LiClO4, CF3SO3Li are preferred, and LiPF6 is particularly preferred. In addition, the supporting electrolyte can be used alone or in combination with two or more in any ratio. There is usually a tendency that the higher the degree of dissociation of the supporting electrolyte, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.
[0185] As an organic solvent for an electrolyte, it is not particularly limited as long as the supporting electrolyte can be dissolved. In the case where, for example, the secondary battery is a lithium ion secondary battery, as an organic solvent, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC) can be preferably used; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these organic solvents can also be used. Among them, because the dielectric constant is high and the stable potential region is wide, carbonates are preferably used.
[0186] In addition, the concentration of the supporting electrolyte in the electrolyte solution can be appropriately adjusted. In addition, a known additive can be added to the electrolyte solution.
[0187] <Spacer>
[0188] As the separator used in the secondary battery of the present invention, the above-mentioned battery member for a secondary battery of the present invention may be used, or a known separator may be used.
[0189] <Method for manufacturing secondary battery>
[0190] The secondary battery of the present invention can be manufactured, for example, by winding, folding, etc. an overlapping body obtained by overlapping a positive electrode, a spacer, and a negative electrode as needed according to the battery shape, placing it in a battery container, injecting an electrolytic solution into the battery container, and sealing it. In addition, as the overlapping body, a battery member for the secondary battery of the present invention can be used as at least one of the positive electrode, the spacer, and the negative electrode, and they can be overlapped and manufactured. Furthermore, in the secondary battery of the present invention, in order to prevent the occurrence of internal pressure rise, overcharge and over-discharge, etc., overcurrent prevention elements such as fuses and PTC elements, porous metal nets, guide plates, etc. can also be provided as needed. The shape of the secondary battery can be any one of, for example, coin type, button type, sheet type, cylindrical type, square type, flat type, etc.
[0191] Examples
[0192] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, in the following description, "%" and "parts" indicating amounts are based on mass.
[0193] In addition, unless otherwise specified, in a polymer manufactured by copolymerizing a plurality of monomers, the proportion of a monomer unit formed by polymerizing a certain monomer in the above polymer is usually the same as the ratio (addition ratio) of the certain monomer in all the monomers used in the polymerization of the polymer.
[0194] Moreover, in the examples and comparative examples, the glass transition temperature, the insoluble component ratio in THF, the volume average particle diameter, the electrolyte swelling degree, the dissolved carbon dioxide concentration, and the coating stability were measured and evaluated according to the following methods.
[0195] <Glass transition temperature (Tg)>
[0196] The granular polymer (A) and the granular polymer (B) prepared in the examples and comparative examples were used as measurement samples, respectively. Weigh 10 mg of the measurement sample in an aluminum dish, and use an empty aluminum dish as a control in a differential thermal analysis measurement device ("EXSTAR DSC6220" manufactured by SII Nanotechnology Inc.). Under the conditions specified in JIS Z 8703, perform the measurement at a heating rate of 10 °C / minute in the measurement temperature range of -100 °C to 500 °C to obtain a differential scanning calorimetry (DSC) curve. The intersection of the baseline immediately before the endothermic peak of the DSC curve where the differential signal (DDSC) becomes 0.05 mW / minute / mg or more during the heating process and the tangent of the DSC curve at the inflection point that first appears after the endothermic peak is taken as the glass transition temperature (°C).
[0197] <Insoluble component ratio in THF>
[0198] The aqueous dispersion of the granular polymer (A) was dried under a humidity of 50% and an environment of 23°C to 25°C to produce a film with a thickness of 3±0.3 mm. The produced film was cut into squares with a side length of 5 mm to prepare a plurality of film pieces, and about 1 g of these film pieces were accurately weighed, and their weight was set as W0 (g). The accurately weighed film piece (weight W0) was immersed in 100 g of tetrahydrofuran (THF) for 24 hours. Then, the film piece was lifted out of THF, and the lifted film piece was vacuum dried at 105°C for 3 hours, and its weight (weight of the insoluble component) W1 (g) was accurately weighed. Then, the insoluble component rate (mass %) in THF was calculated according to the following formula.
[0199] Insoluble content in THF (mass %) = W1 / W0×100
[0200] <Volume Average Particle Size>
[0201] The particle size distribution (volume basis) was measured for an aqueous dispersion of the particulate polymer (A) adjusted to a solid content concentration of 0.1% by mass using a laser diffraction particle size distribution measuring apparatus (manufactured by Beckman Coulter Inc., product name "LS-230"). Then, the particle size at which the cumulative volume calculated from the small particle size side in the measured particle size distribution becomes 50% was taken as the volume average particle size (D50).
[0202] <Electrolyte swelling degree>
[0203] Dry the aqueous dispersion of the granular polymer (A), and press about 0.2 g of the obtained dry product at 200°C and 5 MPa for 2 minutes to obtain a film. Cut the obtained film into squares with a side length of 1 cm as test pieces, and measure the weight W2 (g) of the test piece. Next, immerse the test piece in an electrolyte at 60°C for 72 hours. Then, take out the test piece from the electrolyte, wipe off the electrolyte on the surface, and measure the weight W3 (g) of the test piece. Then, calculate the electrolyte swelling degree (times) according to the following formula. At this time, the electrolyte swelling degree is the value obtained by rounding off the first decimal place.
[0204] Electrolyte swelling degree (times) = W3 / W2
[0205] In addition, as the electrolyte solution for measurement, an electrolyte solution obtained by dissolving LiPF6 as a supporting electrolyte at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and vinylene carbonate (VC) in a volume ratio of EC / DEC / VC=68.5 / 30 / 1.5 was used.
[0206] <Dissolved Carbon Dioxide Concentration>
[0207] A sample was collected in a syringe and injected into a HP6890 gas chromatograph manufactured by Agilent Technologies, Inc., and the dissolved carbon dioxide concentration was measured using a thermal conductivity detector. Quantification was performed by preparing a calibration curve using a standard substance of known concentration.
[0208] <Coating stability>
[0209] [Inkjet coating]
[0210] Using an inkjet slurry feeder with an inkjet head (manufactured by Konica Corporation, product name "KM1024iSAE-C" (shear mode type)), the non-aqueous secondary battery slurry is sprayed onto a black polyester (PET) film at a flight speed of 6 m / sec to 10 m / sec. After the non-aqueous secondary battery slurry coated on the PET film is naturally dried at room temperature, the number of coating points is counted visually. Then, the coating stability (%) is calculated according to the following formula. If the coating stability is 90% or more, the non-aqueous secondary battery slurry has sufficient coating stability required for proper coating on the surface of the battery component using the inkjet method.
[0211] Coating stability (%) = (number of coating points / planned number of coatings) × 100
[0212] (Example 1)
[0213] <Preparation of granular polymer (A)>
[0214] First, in order to form the core part, 88 parts of styrene as an aromatic vinyl monomer, 6 parts of n-butyl acrylate as a (meth)acrylate monomer, 5 parts of methacrylic acid as an acid group-containing monomer, 1 part of ethylene glycol dimethacrylate as a crosslinking monomer, 1 part of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added to a 5 MPa pressure-resistant container equipped with a stirrer, and the mixture was stirred sufficiently, and then the temperature was raised to 60° C. to initiate polymerization. When the polymerization conversion rate reached 96%, 80.7 parts of n-butyl acrylate and 1 part of methacrylic acid as a (meth)acrylate monomer, 18 parts of styrene as an aromatic vinyl monomer, and 0.3 parts of allyl methacrylate as a crosslinking monomer were continuously added to form the shell part, and the temperature was raised to 70° C. to continue polymerization. Then, when the polymerization conversion rate reached 96%, the reaction was terminated by cooling, and an aqueous dispersion (A) containing a particulate polymer (A) was obtained. The glass transition temperature (Tg), the ratio of insoluble components in THF, the volume average particle size, and the electrolyte swelling degree of the particulate polymer (A) were measured using the aqueous dispersion (A).
[0215] <Preparation of granular polymer (B)>
[0216] 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate (Kao Corporation, product name "Emal 2F") as an emulsifier, and 0.5 parts of ammonium persulfate were respectively supplied to a reactor equipped with a stirrer, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0217] On the other hand, in another container, 50 parts of ion exchange water, 0.5 parts of sodium dodecylbenzene sulfonate as an emulsifier, and 94 parts of n-butyl acrylate, 2 parts of acrylonitrile, 2 parts of methacrylic acid, 1 part of N-hydroxymethyl acrylamide and 1 part of allyl glycidyl ether as polymerizable monomers are mixed to obtain a monomer mixture. The monomer mixture is continuously added to the above-mentioned reactor over 4 hours to perform polymerization. During the addition, the reaction is carried out at 60°C. After the addition is completed, the reaction is terminated after further stirring at 70°C for 3 hours to obtain an aqueous dispersion (B) containing an acrylic polymer as a granular polymer (B). The aqueous dispersion (B) is used to measure the glass transition temperature (Tg) of the granular polymer (B). The results are shown in Table 1.
[0218] <Slurry for non-aqueous secondary batteries>
[0219] In a stirring container, 100 parts of an aqueous dispersion (A) containing a granular polymer (A) and 15 parts of an aqueous dispersion (B) containing a granular polymer (B) are mixed in terms of solid content. Ion exchange water is added to the obtained mixed solution to obtain a mixture with a solid content concentration of 15%. The obtained mixture is heated and allowed to stand at a temperature of 35°C for 1 hour to degas the mixture. The dissolved carbon dioxide concentration of the mixture is thereby reduced to obtain a slurry for a non-aqueous secondary battery. The dissolved carbon dioxide concentration in the obtained slurry for a non-aqueous secondary battery is measured to examine the coating stability. The results are shown in Table 1.
[0220] (Example 2)
[0221] The time of heating and standing the mixture obtained in Example 1 was changed to 24 hours. Except for this, the mixture was degassed in the same manner as in Example 1. The dissolved carbon dioxide concentration of the mixture was thereby reduced to obtain a non-aqueous secondary battery slurry. Then, the dissolved carbon dioxide concentration in the obtained non-aqueous secondary battery slurry was measured in the same manner as in Example 1 to examine the coating stability. The results are shown in Table 1.
[0222] (Example 3)
[0223] The time of heating and standing the mixture obtained in Example 1 was changed to 48 hours. Except for this, the mixture was degassed in the same manner as in Example 1. The dissolved carbon dioxide concentration of the mixture was thereby reduced to obtain a non-aqueous secondary battery slurry. Then, the dissolved carbon dioxide concentration in the obtained non-aqueous secondary battery slurry was measured in the same manner as in Example 1 to examine the coating stability. The results are shown in Table 1.
[0224] (Comparative Example 1)
[0225] The mixture obtained in Example 1 was used as a non-aqueous secondary battery slurry without degassing. Then, the dissolved carbon dioxide concentration in the obtained non-aqueous secondary battery slurry was measured in the same manner as in Example 1 to examine the coating stability. The results are shown in Table 1.
[0226] In addition, in Table 1 shown below,
[0227] "BA" represents n-butyl acrylate unit,
[0228] "MAA" means methacrylic acid units,
[0229] "ST" represents styrene unit,
[0230] "AMA" means allyl methacrylate units,
[0231] "EDMA" means ethylene glycol dimethacrylate units,
[0232] "ACL" stands for acrylic acid polymer.
[0233] [Table 1]
[0234]
[0235] According to Table 1, the non-aqueous secondary battery slurries of Examples 1 to 3 obtained by degassing the mixture to reduce the dissolved carbon dioxide concentration of the mixture exhibit high coating stability suitable for coating on the surface of the battery component by inkjet method. In contrast, it can be seen that the non-aqueous secondary battery slurry of Comparative Example 1 obtained without degassing the mixture does not have the coating stability required for coating the non-aqueous secondary battery slurry on the surface of the battery component by inkjet method. Furthermore, according to Examples 2 and 3, it can be considered that when the dissolved carbon dioxide concentration is too low, the coating stability deteriorates.
[0236] Industrial Applicability
[0237] According to the present invention, it is possible to provide a slurry for a non-aqueous secondary battery that can be stably applied to the surface of a battery member by an inkjet method to firmly bond the battery member to other battery members, and a method for producing the same.
[0238] Furthermore, according to the present invention, it is possible to provide a battery member for a non-aqueous secondary battery that can be firmly bonded to other adjacent battery members, and a method for manufacturing the same.
[0239] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery in which battery components are firmly bonded to each other.
Claims
1. A method for producing a slurry for a non-aqueous secondary battery, comprising a degassing step in which the dissolved carbon dioxide concentration of a mixture comprising a particulate polymer (A) and water is reduced, In the degassing step, degassing is performed until the dissolved carbon dioxide concentration of the mixture is 0.01 mg / ml or more and 0.08 mg / ml or less.
2. A slurry for a non-aqueous secondary battery, comprising a particulate polymer (A) and water, The nonaqueous secondary battery slurry has a dissolved carbon dioxide concentration of 0.01 mg / ml or more and 0.08 mg / ml or less.
3. A battery member for a non-aqueous secondary battery, comprising a substrate and a plurality of adhesive materials in the form of dots formed on at least one surface of the substrate, The substrate is a spacer substrate or an electrode substrate, The adhesive material is a dried product of the slurry for non-aqueous secondary batteries according to claim 2 .
4. A method for manufacturing a battery member for a non-aqueous secondary battery, comprising a coating step, in which the slurry for the non-aqueous secondary battery according to claim 2 is coated on a surface of a substrate by an inkjet method, The substrate is a separator substrate or an electrode substrate.
5. The method for producing a battery member for a non-aqueous secondary battery according to claim 4, in, The coating step includes a slurry degassing step of reducing the dissolved carbon dioxide concentration of the slurry for the non-aqueous secondary battery according to claim 2 before the coating step.
6. The method for producing a battery member for a non-aqueous secondary battery according to claim 4 or 5, in, A substrate manufacturing apparatus is used which has at least a supply tank for supplying non-aqueous secondary battery slurry to an inkjet head, a degassing module for reducing the dissolved carbon dioxide concentration of the non-aqueous secondary battery slurry, and an inkjet head for ejecting the non-aqueous secondary battery slurry, and the non-aqueous secondary battery slurry is circulated in the order of the supply tank, the degassing module, and the inkjet head. 7 . A non-aqueous secondary battery comprising the battery component for a non-aqueous secondary battery according to claim 3 .
